OsMKKK70 regulates grain size and leaf angle in rice through the OsMKK4‐OsMAPK6‐OsWRKY53 signaling pathway. Issue 12 (18th October 2021) - Liu, Zhiqi; Mei, Enyang; Tian, Xiaojie; He, Mingliang; Tang, Jiaqi; Xu, Min; Liu, Jiali; Song, Lu; Li, Xiufeng; Wang, Zhenyu; Guan, Qingjie; Xu, Qijiang; et al.
Abstract: Grain size and leaf angle are key agronomic traits that determine final yields in rice. However, the underlying molecular mechanisms are not well understood. Here we demonstrate that the Oryza sativa Mitogen Activated Protein Kinase Kinase Kinase OsMKKK70 regulates grain size and leaf angle in rice. Overexpressing OsMKKK70 caused plants to produce longer seeds. The osmkkk62/70 double mutant and the osmkkk55/62/70 triple mutant displayed significantly smaller seeds and a more erect leaf angle compared to the wild type, indicating that OsMKKK70 functions redundantly with its homologs OsMKKK62 and OsMKKK55. Biochemical analysis demonstrated that OsMKKK70 is an active kinase and that OsMKKK70 interacts with OsMKK4 and promotes OsMAPK6 phosphorylation. In addition, the osmkkk62/70 double mutant showed reduced sensitivity to Brassinosteroids (BRs). Finally, overexpressing constitutively active OsMKK4, OsMAPK6, and OsWRKY53 can partially complement the smaller seed size, erect leaf, and BR hyposensitivity of the osmkkk62/70 double mutant. Taken together, these findings suggest that OsMKKK70 might regulate grain size and leaf angle in rice by activating OsMAPK6 and that OsMKKK70, OsMKK4, OsMAPK6, and OsWRKY53 function in a common signaling pathway that controls grain shape and leaf angle. Abstract : The closely related MAP kinase kinase kinases OsMKKK70, OsMKKK55, and OsMKKK 62 play redundant roles in regulating seed size, flag leaf angle and brassinosteroid sensitivity. OsMKKK70 interacts with the MAP kinase kinase OsMKK4 and promotes OsMAPK6 activity, and might function in same pathway as the OsMKK4–OsMAPK6–OsWRKY53 signaling cascade.